(untitled) (Música Hodie, 2018)
This is the second part of a discussion on the challenges of a second decade of ubimus research. I discuss the issues involved in supporting knowledge transfer in musical activities. I lay out and exemplify the concept of metaphor for creative action. I summarize the results of three studies employing the time tagging metaphor, configuring an effective strategy for supporting everyday musical creativity. Then I report results of a study employing the stripe meta- phor – an extension of time tagging devised for usage of a large number of resources. Twelve subjects, encompassing musicians and casual participants, realized improvisatory sessions in a non-standard setting – an audio and musical equipment store. The results indicated a promising new avenue of research targeting lay-musician interaction. The results also raised new questions regarding the strategies adopted for knowledge transfer support. The last section of the paper places these results within the context of the ongoing ubimus efforts, highlighting four issues that have emerged as viable research avenues: everyday musical creativity, lay-musician interaction, design for sustainability and design for distributed creativity.